Determination of sulfur compounds in gasoline using mercury film electrode by square wave voltammetry - Serafim, Diana Maria [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 2008)
A sensitive method based on square wave voltammetry is described for the quantitative determination of elemental sulfur, disulfide and mercaptan in gasoline using a mercury film electrode. These sulfur compounds can be quantified by direct dissolution of gasoline in a supporting electrolyte followed by subsequent voltammetric measurement. The supporting electrolyte is 1.4 mol L-1 sodium acetate and No acetic acid in methanol. Chemical and optimum operational conditions for the formation of the mercury film were analyzed in this study. The values obtained were a 4.3 mu m thickness for the mercury film, a 1000 rpm rotation frequency, -0.9 V applied potential and 600 s depositing time. Voltammetric measurements were obtained using square wave voltammetry with detection limits of the 3.0 x 10(-9), 1.6 x 10(-7) and 4.9 x 10(-7) mol L-1 for elemental sulfur, disulfide and mercaptan, respectively. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: sulfur compounds; square wave voltammetry; mercury film electrode; gasoline